Pandangan Toshihiko Izutsu Tentang Hukum Islam - arisandy, munib; Tertibi, Yaoma; laili, afrohatul (LPPM UNU BLITAR, 2024)
Islamic law is a complex and in-depth field of study, which requires a structured approach to understand it. One of the figures who made a significant contribution to Islamic law research was Toshihiko Izutsu, a Japanese intellectual who combined philosophical and semantic thinking in his interpretation of the Koran. This research aims to determine Toshihiko Izutzu's views on Islamic law, reviewing his works. The type of research that will be carried out is library research or library research. In library research, library searches are not only used in the initial steps as in field research. The approach used is Toshihiko Izutsu's semantics which aims to support analytical studies of Islamic law through methods compiled regularly by Toshihiko Izutsu, with the aim of obtaining the concept of Islamic law based on Toshihiko Izutsu's views. The conclusion obtained from this comprehensive research is that Toshihiko Izutsu's thoughts on Islamic law can be described as an integration between metaphysical dimensions, inspiration from Ibn Arabi's thoughts, the role of language as a key to understanding, views on justice, and the close relationship between fiqh and morals.